2004
DOI: 10.1159/000079939
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Infarction: The Pathophysiological Concept

Abstract: Cerebral venous occlusion represents an often underdiagnosed cause for acute or slowly progressive neurological deterioration. The underlying pathophysiological basis is not well understood, but is different from those of arterial occlusion reflecting therefore different anatomical and physiological features of the cerebral venous system. Extensive collateral circulation within the cerebral venous system allows for a significant degree of compensation in the early stages of venous occlusion. Elevated cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
169
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(174 citation statements)
references
References 81 publications
4
169
1
Order By: Relevance
“…Human and animal studies examining cerebral venous occlusion have shown that an elevated venous pressure results in a dilatation of upstream venule beds [13,14]. Furthermore, retinal venule dilatation is often associated with ocular venous drainage impairment in certain conditions, such as central retinal vein occlusion or during increased intracranial pressure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Human and animal studies examining cerebral venous occlusion have shown that an elevated venous pressure results in a dilatation of upstream venule beds [13,14]. Furthermore, retinal venule dilatation is often associated with ocular venous drainage impairment in certain conditions, such as central retinal vein occlusion or during increased intracranial pressure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides all these the clinical picture will usually be associated with the underlying disorder/s which contributed to the prothrombotic state. 8,9 Although modern neuroimaging tools specially MRV has enhanced the early detection of VST. 10 The clinical scenario of the present case initially seems to be a presentation of pre-eclampsia due to high blood pressure with headache and diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…10 In present study also 40% in Group 1 and 24.05% patients in Group 2 had moderate hyperhomocysteinemia which supports the findings of Bhaskar et al 10 Homocysteine possess both prothrombotic and atherogenic properties. 11 Higher level of homocysteine elevates oxidative damage by reactive oxygen species. 12 Hyperhomocysteinemia being the risk factor of IS can be an important tool to screen patients with IS who demonstrate no clue for the presence of IS.…”
Section: Discussionmentioning
confidence: 99%